2020
DOI: 10.1101/2020.09.27.315796
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Tethered Ligand Assay to Probe the SARS-CoV-2 ACE2 Interaction under Constant Force

Abstract: The current COVID-19 pandemic has a devastating global impact and is caused by the SARS-CoV-2 virus. SARS-CoV-2 attaches to human host cells through interaction of its receptor binding domain (RBD) located on the viral Spike (S) glycoprotein with angiotensin converting enzyme-2 (ACE2) on the surface of host cells. RBD binding to ACE2 is a critical first step in SARS-CoV-2 infection. Viral attachment occurs in dynamic environments where forces act on the binding partners and multivalent interactions play centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The structure of the RBD–ACE2 complex showed that extensive interactions are formed between RBD and ACE2 ( Lu et al, 2020 ; Bauer et al, 2020 ). To understand the potential role of the RBD mutations in binding to ACE2, we combined a cell-surface-binding assay, a kinetics study, a single-molecule biophysical method, and steered molecular dynamics (SMD) simulations to study the interaction of RBD mutants and ACE2 ( Figure 1D,E ).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the RBD–ACE2 complex showed that extensive interactions are formed between RBD and ACE2 ( Lu et al, 2020 ; Bauer et al, 2020 ). To understand the potential role of the RBD mutations in binding to ACE2, we combined a cell-surface-binding assay, a kinetics study, a single-molecule biophysical method, and steered molecular dynamics (SMD) simulations to study the interaction of RBD mutants and ACE2 ( Figure 1D,E ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of mucin also does not impair the binding of the polymer. In turn, one could predict that the dissociation constant for polyP is even lower than the KD value of the RBD to the cellular ACE2 receptor, which is in the range of ~ 1-100 nM [167]. A cartoon about the binding of mucin-polyP coacervate on the surface of the SARS-CoV-2 is given in Figure 7.I.E-F.…”
Section: Interaction With Mucinmentioning
confidence: 99%
“…For instance, the characterization of the mechanical stability of the RBD of Acute Respiratory Syndrome-novel Coronavirus 2 (SARS-CoV-2) has shown it to be stiffer (greater by 50 pN) compared to SARS-CoV [16]. This result has important consequences during binding to ACE2 (pre-fusion state) [17], as it can withstand Brownian and cellular forces and yet maintains close contact while priming of the spike protein by transmembrane protease serine 2 (TMPRSS2) occurs as part of S1 dissociation from S2 that enables the post-fusion mechanism [17,18]. In addition, in silico studies found a space correlation between the polybasic furin cleavage site Q 677 TNSPRRAR↓SV 687 and surface residues located in the RBD region that recognize the ACE2 in SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%